2022
DOI: 10.3390/biom12060803
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cell-Derived Microvesicles in Hematological Diseases and beyond

Abstract: Microvesicles or ectosomes represent a major type of extracellular vesicles that are formed by outward budding of the plasma membrane. Typically, they are bigger than exosomes but smaller than apoptotic vesicles, although they may overlap with both in size and content. Their release by cells is a means to dispose redundant, damaged, or dangerous material; to repair membrane lesions; and, primarily, to mediate intercellular communication. By participating in these vital activities, microvesicles may impact a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 211 publications
0
12
0
Order By: Relevance
“…Almost all eukaryotic cells including erythrocytes and platelets, are capable of releasing MPs. The mechanisms of MP production and release and their biological functions have been intensively studied [ 41 , 42 ]. MP release from nucleated cells usually occurs during activation or early apoptosis as well as due to cell differentiation, stress, senescence, stimulation by external cytokines or shear forces, ATP (adenosine triphosphate) treatment, apoptosis, microenvironmental changes, hypoxia, and malignancy.…”
Section: Ev Isolation Methodsmentioning
confidence: 99%
“…Almost all eukaryotic cells including erythrocytes and platelets, are capable of releasing MPs. The mechanisms of MP production and release and their biological functions have been intensively studied [ 41 , 42 ]. MP release from nucleated cells usually occurs during activation or early apoptosis as well as due to cell differentiation, stress, senescence, stimulation by external cytokines or shear forces, ATP (adenosine triphosphate) treatment, apoptosis, microenvironmental changes, hypoxia, and malignancy.…”
Section: Ev Isolation Methodsmentioning
confidence: 99%
“…Recent cell-based theories, together with groundbreaking findings involving extracellular vesicles (EV), have sought to provide a holistic explanation of the intricate mechanisms inherent in in vivo coagulation. There is increasing evidence that cell- and platelet-derived EVs, which comprise microvesicles (MVs), exosomes, and apoptotic bodies, play an important role in the modulation of the coagulation cascade during hemostasis and thrombosis [ 37 , 38 , 39 ].…”
Section: Hemostasis and Its Regulationmentioning
confidence: 99%
“…These experiments also confirmed that Hb mediated oxidation of band 3 triggers band 3 clustering and microparticle (MP) formation and release from mother cells. MPs are miniature RBCs containing almost all the elements of mature RBCs, including Hb (for review, see 37 ).…”
Section: Oxidation Reactions Of Cellular Hemoglobin In Health and In ...mentioning
confidence: 99%